1995
DOI: 10.1159/000113542
|View full text |Cite
|
Sign up to set email alerts
|

Brain Size and Morphology in Miniaturized Plethodontid Salamanders

Abstract: In six miniaturized salamanders of the family Plethodontidae, including one of the smallest tetrapod vertebrates, Thorius pennatulus, the anatomical consequences of miniaturization for the brain were investigated. We determined (1) absolute and relative size of the brain, major parts of the brain, the tectum and tectal gray matter, (2) nerve cell size and density, and (3) the number of cells within the visual and visuomotor centers (thalamus, tectum/praetectum and tegmentum). No common compensatory strategy fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 4 publications
0
16
0
1
Order By: Relevance
“…Many studies have shown that cell size among species is strongly positively correlated with genome size (24,(51)(52)(53), and may, at least in Amphibia, affect organ complexity and size (8,(53)(54)(55). But the positive relationship between genome and cell size, although widespread, is not universal.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that cell size among species is strongly positively correlated with genome size (24,(51)(52)(53), and may, at least in Amphibia, affect organ complexity and size (8,(53)(54)(55). But the positive relationship between genome and cell size, although widespread, is not universal.…”
Section: Discussionmentioning
confidence: 99%
“…The many examples in which genes have been shown to be associated with phenotypes tend to lack hypotheses yielding expectations on how gene variants yield different phenotypes. Micro-and macroscopic levels of analysis were shown to meet in salamanders and frogs: genome size, through its effects on cell size, apparently affects regeneration rate (Sessions and Larsson, 1987), brain structure (Roth et al, 1994) and evolutionary trends towards miniaturization (Roth et al, 1995). Numbers of repetitive elements in developmental genes correlate with vertebrate limb and skull morphologies (Fondon and Garner, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…While at the same time, an association of small body size with a relatively large or unaltered cell size occurs in groups that evolved toward small sizes more recently (e.g. in plethodontid salamanders (Roth et al 1994(Roth et al , 1995). …”
Section: Discussionmentioning
confidence: 99%